Factors Influencing Mortgage Decision Making: Financial Inclusion as Mediation Variable - Albiansyah Margana Putra; Ikka Nabila; Mardiyani Mardiyani (Universitas Airlangga, 2025)
Background: Indonesia is a developing country with low social welfare. Its small per capita income level, high consumptive spending, and high property prices make decent housing difficult, which is an important factor in our research. Objective: This research aimed to comprehensively examine the factors that affect Mortgage Decision-Making among people in Cirebon Regency. Method: Data was collected on the community in Cirebon City through a survey using a Google Form distributed to respondents online and offline. A causal associative method was implemented for this research, with a sample of 190 respondents chosen from purposive sampling, with the criteria of having previously taken out or planning to take out a Home Ownership Credit. SEM-PLS version 3.0 was utilized for data analysis. Results: The research findings revealed that Financial Literacy does not significantly influence Mortgage decision-making, while Financial Planning does. The other findings indicated that Financial Inclusion cannot mediate the relationship between Financial Literacy and Financial Planning on Mortgage Decision-Making. Conclusion: Financial inclusion is an indicator of financial literacy and financial planning. It can be proven that other factors, such as social factors, community psychology, and community confidence, must be improved in reaching a mortgage credit decision. The role of the government is also very important in this case; providing learning about financial literacy is one alternative to increasing public awareness. Keywords: Financial Literacy; Financial Planning, Financial Inclusion, Mortgage Decisions, Home Ownership Credit